"Pocketing" Research Data? Ethnographic Data Production as Material Theorizing. (February 2021) - Neubert, Christine; Trischler, Ronja
We analyze the relations between ethnographic data and theory through an examination of materiality in research practices, arguing that data production is a form of material theorizing. This entails reviewing and (re-)applying practice-theoretical discussions on materiality to questions of ethnography, and moving from understanding theory primarily as ideas to observing theorizing in all steps of research practice. We introduce "pocketing" as a heuristic concept to analyze how and when ethnographic data materializes: the concept defines data's materiality relationally, through the affective and temporal dimensions of practice. It is discussed using two examples: in a study on everyday architectural experience where ethnographic data materialized as bodies affected by architecture; and in a study on digital cooperation where research data's materialization was distributed over time according to the use of a company database. By conceptualizing data's materiality as practice-bound, "pocketing" facilitates understanding the links between data and theory in ethnographic data production.